Midwifery Students’ Experiences of Mentorship at the Korle-Bu Teaching Hospital - Oduro-Arhin, A.J. (University Of Ghana, 2018)
Mentorship is a critical process that supports mentee learning and skills acquisition during clinical practicum. It has been adopted by many high-income countries to assist students in clinical placements. The number of experienced midwives continue to diminish while the midwifery student who is the future frontline health worker is left to stand alone. Benefits of mentorship which include knowledge and skills acquisition and career satisfaction, prepare the student for the delivery of quality Maternal and Child Health care (MCH). However, there is a paucity of research evidence on midwifery mentorship in Africa, particularly Ghana. The purpose of the study was to explore midwifery students’ experiences about mentorship during clinical practicum at the Korle-Bu Teaching Hospital (KBTH). A qualitative exploratory descriptive design was employed to explore the phenomenon of midwifery mentorship. A purposive sampling technique was used to recruit eleven participants who informed the study. Data were collected with a semi-structured interview guide. Data were analysed concurrently with data collection using thematic content analysis. Anonymity and confidentiality were ensured. Wanberg et al. conceptual framework of mentoring relationships was used to guide the work. Seven main themes emerged from the analysis of data. The findings from the study suggest that the mentorship and skills acquisition during clinical practicum is not well established in the midwifery training college. Mentorship will be beneficial to the students if a good relationship is established between the mentor and mentee. Other clinical staff members should be willing to support students in learning. The study concluded that mentorship requires attention in order to enhance knowledge and skills acquisition, build the confidence of midwifery students and improve maternal and child health. Keywords: Mentorship, Experiences, Mentor, Midwifery Student, Clinical Practicum.
MPhil.
Keywords: Mentorship; Midwifery Student; Clinical Practicum; Korle-Bu Teaching Hospital